Compatibility And Biodegradability Of Biopolyester-Based Blends With Poly(3-Hydroxybutyrate-Co-3-Hydroxyhexanoate) (Phbh) As A Blend Matrix - Jeepery, Iffa Farahin (2024)
Poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (phbh) has been evaluated to have excellent degradability in marine environment. However, its performance for application is still limited. A series of properties enhancement is deemed necessary to improve the potential of phbh being both a high-performance material and readily biodegradable. In this study, phbh containing 5 and 17 mol% 3-hydroxyhexanoate (3hh) were blended with atactic poly(3-hydroxybutyrate) (phb), polycaprolactone (pcl), and polybutylene succinate (pbs) at different ratios by the solvent-casting method. Phbh-5%/atactic phb and phbh-17%/atactic phb showed a single glass-transition temperature (tg), indicating miscibility in the amorphous state. Immiscibility was observed in the phbh-5%/pcl and phbh-17%/pcl blends based on the non-transitioning tg of the phbh component, presence of two distinct tg values for some of the blend films, and individual crystallization manner. The thermal properties and spherulitic morphologies of the phbh-5%/pbs blend films suggested partial miscibility. The enzymatic degradability of the three types of blends by ralstonia pickettii t1 phb depolymerase and burkholderia cepacia lipase was investigated. Depending on the enzyme–substrate specificity, miscibility, and phase structure of the blend, the enzymatic erosion rate was different among the three types of blends.